Overview of Emergency Case Management Capability at PONED Puskesmas X - Siyania, Piya; Tanesib, Amran Julianto; Fikawati, Sandra (jitek, 2025)
X Health Center UPTD, which is located in an urban area, is categorized as a Non-Inpatient Health Center with the capability of Basic Emergency Neonatal Obstetric Services (PONED) and 24 hours Emergency Services. This study aims to evaluate the ability to handle maternal and neonatal emergencies at PONED UPTD X Health Center. This research uses qualitative methods by conducting in-depth interviews with health workers (1 Doctor, 1 Midwife, 1 Nurse and 1 patient) and direct observation of infrastructure. The research was conducted from May to June 2024. The results of the study show that in PONED facilities there are still limitations in resuscitation equipment and certain drugs. Only 13.6% of the support team has attended PONED training. Limited staff of doctors and laboratory analysts hampers 24-hour service. Although there has been an increase in deliveries and a decrease in referrals, some cases should be treated without referral. There is an important role of social support and collaboration in improving services. There is a need to increase the number of trained health workers, continuous training, provision of medical equipment and medicines and increased collaboration with referral facilities.